1999
DOI: 10.1038/6535
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the poly(ADP-ribose) polymerase gene are resistant to pancreatic beta-cell destruction and diabetes development induced by streptozocin

Abstract: Human type 1 diabetes results from the selective destruction of insulin-producing pancreatic beta cells during islet inflammation. Cytokines and reactive radicals released during this process contribute to beta-cell death. Here we show that mice with a disrupted gene coding for poly (ADP-ribose) polymerase (PARP-/- mice) are completely resistant to the development of diabetes induced by the beta-cell toxin streptozocin. The mice remained normoglycemic and maintained normal levels of total pancreatic insulin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
238
3
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(251 citation statements)
references
References 40 publications
6
238
3
4
Order By: Relevance
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 91%
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 91%
“…Also, mice deficient in PARP are resistant to beta cell death mediated by streptozotocin, in spite of DNA fragmentation. The absence of PARP prevents the depletion of the cofactor NAD + and the subsequent loss of ATP [84,[88][89][90] and thus cell death.…”
Section: Beta Cell Toxicity Of Streptozotocinmentioning
confidence: 99%
“…Multiple subdiabetogenic doses of STZ provoke different changes in the pancreas from a single injection of a diabetogenic dose of STZ [17,18,19] and enable us to observe the re-organization of pancreatic beta cells [20]. Thus, multiple low doses of STZ are considered to create a good model for observing regeneration after beta-cellspecific injury.…”
mentioning
confidence: 99%